Analisis Kesulitan Mahasiswa Statistika Universitas Negeri Medan Dalam Penulisan Artikel Ilmiah - Sinaga, Anita; Putri, Aulia Kusuma; Sinaga, Kezia Theodora; Deswan, Meisyy Laisa Usrini; Putri, Maharani Renika; Dalimunthe, Syairal Fahmy (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
This study aims to explore the challenges faced by students of the Statistics Study Program at Universitas Negeri Medan in the process of writing scientific articles. Previous research has shown that these difficulties are related to motivation, time, and access to references. The method applied in this study is a survey using a questionnaire. The findings indicate the importance of enhancing academic guidance, training in scientific writing, and utilizing technology to support the writing process. The conclusion emphasizes that support from academic institutions is essential in helping students overcome these difficulties, enabling them to produce scientific articles that meet the expected academic standards.